Comparative studies of bone density by quantitative ultrasound (QUS) with dual-energy X-ray absorptiometry (DEXA) scan - Rajouria, Alark Devkota; Bhattarai, Madur Dev; Bajracharya, Manil Ratna; Karki, Buddha Bahadur (Journal of Chitwan Medical College, 2019)
Background: The aim of the study was to establish the correlation quantitative ultrasound (QUS) between and dual-energy X-ray absorptiometry (DEXA) and to assess the ability of QUS as a screening tool for osteoporosis. Methods: The study was conducted on 115 patients. All the patients underwent QUS of radius using Sunlight MiniOmni bone sonometer and DEXA screening for measurement of bone mineral density (BMD) at lumbar spine, total left & femoral neck and radius. Results: Significant correlations were observed between QUS and DEXA T score. Conclusions: QUS is a sensitive screening tool to detect changes in the bone mass and risk of osteoporosis.